Petrocosmea albocaerulea (Gesneriaceae), a new species from northwestern Vietnam - Thien, Tran Duc; Quang, Bui Hong; Anh, Tran Thi Phuong; Hai, Do Van; Nuraliev, Maxim S. (Phytotaxa, 2024)
Petrocosmea albocaerulea, a new species of Gesneriaceae, is described and illustrated. The species was discovered in 2018 and 2023 during botanical surveys in two neighboring northwestern provinces of Vietnam, close to the tri-border area of Vietnam, China and Laos. Petrocosmea albocaerulea is distinct from its congeners by the following features: several-flowered inflorescences, corolla with white tube and light blue lobes, corolla glabrous inside, corolla lobes not longer than the tube, glabrous stamen filaments, anthers rounded at the apex, and style hairy near base and glabrous otherwise. A need for a thorough reconsideration of the sectional subdivision of Petrocosmea is highlighted.